Quota System in Pakistan – A Critical Analysis - Memon, Qurat-ul-Ain (Journal of Pakistan Administration, 2021)
The basic purpose of quota system is to be ensured by the governments that if at any specific time period, if the entire population couldn’t be guaranteed to have uniform access to opportunities of growth and development at par with each other; with respect to their distinct region, terrain, population and available facilities including physical infrastructure, then the implementation of quota system would be ensured so that people belonging to different regions may not lose the opportunities of getting government employment.
Keywords: Quota System; Pakistan; Critical Analysis; Population; opputunities